Necrotizing pneumonia requiring prolonged extracorporeal membrane oxygenation: Pushing the boundaries in pediatric ECMO - Pravin R. R.; Suresh Chandran; Yi Hua Tan; Biju Thomas; Jan Hau Lee; Anuradha P. Menon; Kim Kiat Ong; Arun Kumar Pugalenthi (Clinical Case Reports, 2022)
Abstract Extracorporeal membrane oxygenation (ECMO) is a life‐saving rescue therapy used in acute respiratory failure refractory to invasive mechanical ventilation. Recent studies on positive outcomes of extended ECMO therapy are promising. We describe a case of a 2‐year 8‐month‐old female child with necrotizing pneumonia secondary to Streptococcus pneumoniae, Influenza A, and Mycoplasma pneumoniae, who survived with intact neurological function and no long‐term adverse outcomes after a prolonged ECMO run of 86 days. To the best of our knowledge, this is one of the longer durations of ECMO with transplant‐free survival in a pediatric patient requiring respiratory support with good recovery and a good functional outcome. Allowing time for native lung recovery is pivotal for optimal recovery, despite significant lung injury due to the underlying disease process. With evolving ECMO experience, clinicians may need to re‐consider the conventional maximum duration of ECMO in children with severe respiratory failure on a case‐by‐case basis.